PROTOCOL CONVERSION BETWEBN ADLP 80 AND IEC 870 COMMUNICATION PROTOCOL STANDARDS USING FORMAL METHODS (Journal of Engineering, 2003)
In this work, a protocol converter had been designed using formal methods in order to make a controlling station that supports ADLP 80 (ASEA) protocol stanclard able to communicate with a controlled station that utilizls another communication protocol called IEC 870 protocol standard, in a central control system. The two protocols are modeled using communicating finite state machine (CFSM) models. For simplicity, i converter is constructed for each application function using a conversion algorithm. Thii algorithm adopts a protocol data unit approach to derive the converter machine.